A review of mechanism and adsorption capacities of biochar-based engineered composites for removing aquatic pollutants from contaminated water - Murtaza, Ghulam; Ahmed, Zeeshan; Dai, Dong-Qin; Iqbal, Rashid; Bawazeer, Sami; Usman, Muhammad; Rizwan, Muhammad; Iqbal, Javed; Akram, Muhammad Irfan; Althubiani, Abdullah Safar; Tariq, Akash; Ali, Iftikhar (Frontiers in Environmental Science, 2022)
Water contamination by aquatic pollutants (antibiotics, heavy metals, nutrients, and organic pollutants) has become the most serious issue of recent times due to associated human health risks. Biochar (BC) has been deemed an effective and promising green material for the remediation of a wide range of environmental pollutants. Due to its limited properties (small pore size and low surface functionality), pristine BC has encountered bottlenecks in decontamination applications. These limitations can be rectified by modifying the pristine BC into engineered BC via multiple modification methods (physical, chemical, and mechanical), thus improving its decontamination functionalities. Recently, these engineered BCs/BC-based composites or BC composites have gathered pronounced attention for water decontamination due to fewer chemical requirements, high energy efficiency, and pollutant removal capacity. BC-based composites are synthesized by mixing BC with various modifiers, including carbonaceous material, clay minerals, metals, and metal oxides. They considerably modify the physiochemical attributes of BC and increase its adsorption ability against various types of aquatic pollutants. BC-based composites are efficient in eliminating target pollutants. The efficiency and type of a specific mechanism depend on various factors, mainly on the physicochemical characteristics and composition of the BC-based composites and the target pollutants. Among the different engineered BCs, the efficiency of clay-BC composites in removing the antibiotics, dyes, metals, and nutrients was good. This review could help develop a comprehensive understanding of using engineered BCs as effective materials for the remediation of contaminated water. Finally, gaps and challenges in research are identified, and future research needs are proposed.